2021
DOI: 10.1074/jbc.ra120.015413
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing p97 inhibitors for chemical modulation of the bacterial ClpB–DnaK bichaperone system

Abstract: The ClpB/DnaK bi-chaperone system reactivates aggregated cellular proteins and is essential for survival of bacteria, fungi, protozoa, and plants under stress. AAA+ ATPase ClpB is a promising target for the development of antimicrobials, because a loss of its activity is detrimental for survival of many pathogens and no apparent ClpB orthologs are found in metazoans. We investigated ClpB activity in the presence of several compounds that were previously described as inhibitor leads for the human AAA+ ATPase p9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 75 publications
(95 reference statements)
2
17
0
Order By: Relevance
“…Currently, only a few ClpB inhibitors have been identified (Grimminger et al, 2004;Martin et al, 2013;Kuczynska-Wisnik et al, 2017;Glaza et al, 2020;Singh et al, 2020). Guanidinium chloride specifically inhibits the ATP hydrolysis by Hsp104 of Saccharomyces cerevisiae and also the ClpB function of Ehrlichia chaffeensis (Grimminger et al, 2004).…”
Section: Clpb As a Therapeutic Targetmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, only a few ClpB inhibitors have been identified (Grimminger et al, 2004;Martin et al, 2013;Kuczynska-Wisnik et al, 2017;Glaza et al, 2020;Singh et al, 2020). Guanidinium chloride specifically inhibits the ATP hydrolysis by Hsp104 of Saccharomyces cerevisiae and also the ClpB function of Ehrlichia chaffeensis (Grimminger et al, 2004).…”
Section: Clpb As a Therapeutic Targetmentioning
confidence: 99%
“…ClpB is highly conserved amongst bacteria, fungi, protozoa, and plants and its role under different stressful conditions has been much studied. It provides protection against, e.g., heat, low pH, osmotic-and oxidative stress, ethanol, and nutrient starvation (Meibom et al, 2008;Krajewska et al, 2017;Glaza et al, 2020;Tripathi et al, 2020). Thus, clpB-deficient mutants demonstrate tremendously decreased survival upon exposure to these stresses.…”
Section: Introduction and Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study explored the hypothesis that known small-molecule ligands of AAA+ ATPases might also interact with ClpB. Among three inhibitors of the human AAA+ ATPase p97, a promising antitumor target, only one affected ClpB [ 73 ]. The identified compound, N 2 ,N 4 -dibenzylquinazoline-2,4-diamine (DBeQ) has been previously used as an antimicrobial [ 74 , 75 ], but without clear identification of its cellular targets.…”
Section: Clpb As a Druggable Targetmentioning
confidence: 99%
“…The identified compound, N 2 ,N 4 -dibenzylquinazoline-2,4-diamine (DBeQ) has been previously used as an antimicrobial [ 74 , 75 ], but without clear identification of its cellular targets. It has now been shown that ClpB is the main target of DBeQ in E. coli under both permissive conditions and during heat stress [ 73 ]. Thus, ClpB can be selectively targeted with a small-molecule ligand in bacterial cells and such a treatment could produce a loss of bacterial viability.…”
Section: Clpb As a Druggable Targetmentioning
confidence: 99%